Clean eating's surprising normalisation: The case of Nigella Lawson. (June 2020) - Smith, Angela
Abstract: Clean eating as a dietary form of 'good food' has grown in popularity in the last decade. This article explores how it has come to be associated with certain ingredients and a general discourse of wellbeing. Whllst being largely discredited as psuedo-science, many of these ingredients have found their ways into recipes in the cookery books of those who declare a clear opposition to clean eating. In particular, the cookery books of Nigella Lawson will be explored as she states a preference for new ingredients that are typically associated with clean eating.